Method for improving corrosion resistance of steel bars in concrete

By electrodeposition in the inorganic salt solution, forming an inorganic salt protective layer, combining cathode current and anode material, the environmental pollution and high cost problems in the preparation of existing reinforced concrete corrosion-resistant coatings are solved, and the efficient corrosion resistance of the steel bars is achieved and Simple process, suitable for a wide range of applications.

CN119121356APending Publication Date: 2024-12-13ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411264925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing corrosion-resistant coating preparation methods for reinforced concrete have problems such as environmental pollution, high cost and complex construction processes, and it is difficult to maintain low cost and high efficiency in wide applications.

Method used

By electrodeposition in the inorganic salt solution, an inorganic salt protective layer is formed, combining cathode current and anode material, the corrosion resistance of the steel bar surface is improved, and the process flow is simplified, using water as a solvent to reduce costs.

Benefits of technology

It significantly improves the corrosion resistance of steel bars and bond strength to concrete, simplifies the process flow, reduces the risk of environmental pollution, and is suitable for applications under a wide range of engineering conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121356A_ABST
    Figure CN119121356A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving corrosion resistance of reinforcing steel bars in concrete. According to the method for improving the corrosion resistance of the reinforcing steel bars in the concrete, the self-corrosion potential of the reinforcing steel bars can be improved by applying cathode current to the reinforcing steel bars, and the corrosion resistance is improved; an inorganic salt protective layer is formed on the surface after electro-deposition in an inorganic salt solution, so that the corrosion resistance of the steel bar is further improved; the bonding strength between inorganic salt deposited through electrochemical reaction and a reinforcing steel bar matrix is high, and the surface layer of the inorganic salt is rough, so that the bonding force between the reinforcing steel bar and concrete can be relatively improved; the inorganic salt solution takes water as a solvent, is pollution-free and low in cost and is suitable for popularization and application; the treatment method is simple, convenient and efficient, and can be popularized under general engineering conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of reinforced concrete protection, and in particular to a method for improving the corrosion resistance of steel bars in concrete. Background Art

[0002] Reinforced concrete is the most widely used material in civil engineering. Therefore, the durability of reinforced concrete is of vital importance. Steel bar corrosion is the main reason for the decline in the durability of reinforced concrete structures. In response to the problem of steel bar corrosion, the current main approach is to "focus on prevention and combine prevention and treatment". In the vast areas containing chloride ions, chloride ion erosion is the main factor leading to steel bar corrosion.

[0003] The prior art discloses a method for electrophoretic deposition of graphene coating on a carbon steel substrate, wherein the graphene nano-fragments are doped with concentrated hydrochloric acid, and H-doped graphene nano-fragments are obtained after filtration; the H-doped graphene nano-fragments are then placed in a mixed organic solvent of N-methylpyrrolidone / acetonitrile, subjected to ultrasonic treatment, and then magnetically stirred to obtain a dispersed graphene colloidal solution; the dispersed graphene colloidal solution is then used as an electrolyte to deposit the graphene coating on the carbon steel substrate by electrophoretic deposition. However, the colloidal solution used in this method is an organic solution, which is prone to environmental pollution, and the solution preparation method is complex and costly.

[0004] The prior art discloses a steel bar corrosion-resistant coating for marine engineering concrete and a preparation method thereof. By adding self-repairing corrosion microcapsules, metal powder, and graphene oxide powder to the electrophoretic coating, the corrosion resistance of the coating can be significantly improved through the self-repairing property of the self-repairing microcapsules and the combined effect of cathodic protection. The corrosion-resistant coating has excellent adhesion and corrosion resistance, and can extend the service life of the steel bar. However, the complex preparation of the colloidal solution and the use of self-repairing microcapsules in this method increase the application cost of the method. The complexity of the solution complicates the construction process during the application process, and it does not have the advantages of convenience and low cost.

[0005] Based on the defects in the preparation of current steel bar corrosion-resistant coatings, it is necessary to improve this. Summary of the invention

[0006] In view of this, in order to address the above-mentioned deficiencies in the prior art, the present invention provides a method for improving the corrosion resistance of steel bars in concrete. After treatment by this method, a point-deposited salt protective layer will be formed on the surface of the steel bars, which greatly improves the corrosion resistance of the steel bars. In addition, the microstructure of the deposited surface is uneven. When preparing reinforced concrete components, there is a physical effect of mechanical bite between the two, which improves the bonding strength between the steel bars and the concrete matrix.

[0007] The details of this plan are as follows:

[0008] The present invention provides a method for improving the corrosion resistance of steel bars in concrete, comprising the following steps:

[0009] Adding an inorganic salt into water to prepare an inorganic salt solution;

[0010] The steel bar is placed in an inorganic salt solution, and an anode material is placed in the inorganic salt solution;

[0011] The steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to perform electrodeposition to form an inorganic salt protective layer on the surface of the steel bar;

[0012] Wherein, the inorganic salt includes at least one of calcium sulfate, zinc sulfate, sodium sulfate, calcium chloride and calcium acetate.

[0013] Preferably, the concentration of the inorganic salt in the inorganic salt solution is 0.1-2 mol / L.

[0014] Preferably, the process parameters of electrodeposition control are: cathode current density is 0.75-5A / m 2 , the deposition time is 1 to 24 hours, the temperature of the inorganic salt solution is 20 to 30°C, and the maximum power supply voltage does not exceed 50V.

[0015] Preferably, before placing the steel bars in the inorganic salt solution, the steel bars are also pre-treated, and the pre-treatment includes: degreasing, pickling, water washing, and sandblasting the steel bars in sequence for use.

[0016] Preferably, the degreasing process is as follows:

[0017] Place the steel bars in an alkali solution and perform ultrasonic treatment at 20-30°C.

[0018] Preferably, the pickling is specifically:

[0019] Soak the degreased steel bars in a hydrochloric acid solution with a concentration of 0.1 to 0.2 mol / L for 10 to 20 minutes.

[0020] Preferably, the alkali solution includes at least one of a sodium hydroxide solution, a sodium carbonate solution, a sodium phosphate solution, and a sodium silicate solution;

[0021] The mass concentration of the alkali solution is 2 to 10%;

[0022] The ultrasonic treatment time is 10 to 15 minutes.

[0023] Preferably, after the inorganic salt protective layer is formed on the surface of the steel bar, the steel bar is further washed and dried;

[0024] The drying temperature is 30-50°C and the drying time is 15-60 minutes.

[0025] Preferably, the distance between the steel bar and the anode material is 10 to 50 cm.

[0026] Preferably, the anode material includes at least one of graphite and stainless steel.

[0027] The method of improving the corrosion resistance of steel bars in concrete of the present invention has the following beneficial effects compared with the prior art:

[0028] The method for improving the corrosion resistance of steel bars in concrete of the present invention can improve the self-corrosion potential and the corrosion resistance of the steel bars by passing a cathode current through the steel bars; an inorganic salt protective layer is formed on the surface after electrodeposition in an inorganic salt solution, which further improves the corrosion resistance of the steel bars; the inorganic salt deposited by the electrochemical reaction has a high bonding strength with the steel bar matrix, and the rough surface of the inorganic salt can relatively improve the bonding strength between the steel bars and the concrete; the inorganic salt solution uses water as a solvent, is pollution-free and has a low cost, and is suitable for popularization and use; the treatment method is simple and efficient, and can be popularized under general engineering conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 The surface morphology of the steel bar before the electrodeposition treatment and after the treatment according to the method in Examples 1 to 2;

[0031] Figure 2 It shows the surface micro-morphology of the steel bar which has not been treated by electrodeposition and the steel bar treated by the method in Examples 1 to 2 after being placed in a salt spray environment for 7 days;

[0032] Figure 3 is the linear polarization curve of the steel bar before electrodeposition treatment;

[0033] Figure 4 is the linear polarization curve of the steel bar after being treated according to the method in Example 1;

[0034] Figure 5 is the linear polarization curve of the steel bar after being treated according to the method in Example 2. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0037] The present invention provides a method for improving the corrosion resistance of steel bars in concrete, comprising the following steps:

[0038] S1. Adding an inorganic salt into water to prepare an inorganic salt solution;

[0039] S2, placing the steel bar in an inorganic salt solution, and placing an anode material in the inorganic salt solution;

[0040] S3, connecting the steel bar and the anode material to the negative electrode and the positive electrode of the power supply respectively, and performing electrodeposition to form an inorganic salt protective layer on the surface of the steel bar;

[0041] Wherein, the inorganic salt includes at least one of calcium sulfate, zinc sulfate, sodium sulfate, calcium chloride and calcium acetate.

[0042] The method for improving the corrosion resistance of steel bars in concrete of the present invention can improve the self-corrosion potential and the corrosion resistance of the steel bars by passing a cathode current through the steel bars; an inorganic salt protective layer is formed on the surface after electrodeposition in an inorganic salt solution, which further improves the corrosion resistance of the steel bars; the inorganic salt deposited by the electrochemical reaction has a high bonding strength with the steel bar matrix, and the rough surface of the inorganic salt can relatively improve the bonding strength between the steel bars and the concrete; the inorganic salt solution uses water as a solvent, is pollution-free and has a low cost, and is suitable for popularization and use; the treatment method is simple and efficient, and can be popularized under general engineering conditions.

[0043] In some embodiments, the concentration of the inorganic salt in the inorganic salt solution is 0.1-2 mol / L.

[0044] Specifically, the preparation method of the inorganic salt solution is: calcium sulfate, zinc sulfate, sodium sulfate, calcium chloride, calcium acetate and other water-soluble inorganic salts, if the inorganic salt solution is a single inorganic salt solution, directly add the single salt into 60-100°C water and mix, use a high-speed stirrer to stir for 10-30 minutes, let it fully dissolve and then cool to room temperature for use; the concentration of the single salt solution is a molar concentration of 0.1-2 mol / L. If the inorganic salt solution is a mixture of multiple inorganic salts, it is necessary to first add water to the single salt solution to prepare a single salt solution with the same molar concentration, the molar concentration is 0.1-2 mol / L, and then stir and mix in different proportions to form a mixture of multiple inorganic salts. It is required that multiple inorganic salts will not precipitate with each other after being dissolved in water.

[0045] In some embodiments, the process parameters of electrodeposition control are: cathode current density is 0.75-5A / m 2 , the deposition time is 1 to 24 hours, the temperature of the inorganic salt solution is 20 to 30°C, and the maximum power supply voltage does not exceed 50V.

[0046] In some embodiments, before placing the steel bars in the inorganic salt solution, the steel bars are also pre-treated, and the pre-treatment includes: degreasing, pickling, water washing, and sandblasting the steel bars in sequence for use.

[0047] In some embodiments, degreasing is specifically:

[0048] Place the steel bars in an alkali solution and perform ultrasonic treatment at 20-30°C.

[0049] In some embodiments, pickling is specifically:

[0050] Soak the degreased steel bars in a hydrochloric acid solution with a concentration of 0.1 to 0.2 mol / L for 10 to 20 minutes.

[0051] In some embodiments, the alkali solution includes at least one of a sodium hydroxide solution, a sodium carbonate solution, a sodium phosphate solution, and a sodium silicate solution.

[0052] In some embodiments, the mass concentration of the alkali solution is 2-10%.

[0053] In some embodiments, the ultrasonic treatment time is 10 to 15 minutes.

[0054] In some embodiments, after the inorganic salt protective layer is formed on the surface of the steel bar, the steel bar is further washed and dried;

[0055] The drying temperature is 30-50°C and the drying time is 15-60 minutes.

[0056] In some embodiments, the distance between the steel bar and the anode material is 10-50 cm.

[0057] In some embodiments, the anode material includes conductive materials such as graphite and stainless steel, and is generally in the shape of a strip.

[0058] The following further illustrates the method for improving the corrosion resistance of steel bars in concrete of the present invention with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0059] Example 1

[0060] This embodiment provides a method for improving the corrosion resistance of steel bars in concrete, comprising the following steps:

[0061] S1. Pre-treat the surface of the steel bar: the steel bar is degreased, pickled, washed, and sandblasted before use; the degreasing step is to ultrasonically clean the steel bar in a sodium hydroxide solution with a mass concentration of 5% for 15 minutes at a degreasing temperature of 30°C; the pickling step is to soak the degreased steel bar in a 0.2 mol / L dilute hydrochloric acid solution for 10 minutes;

[0062] S2. Prepare an inorganic salt solution: add sodium sulfate to water to prepare a 0.5 mol / L sodium sulfate solution;

[0063] S3, cathode electrodeposition: placing the steel bar in a sodium sulfate solution and placing the anode material in an inorganic salt solution; connecting the steel bar and the anode material to the negative electrode and the positive electrode of a power source respectively, and performing electrodeposition to form an inorganic salt protective layer on the surface of the steel bar;

[0064] The process parameters of electrodeposition control are: cathode current density is 1.0A / m 2 , the deposition time is 1h, the temperature of the inorganic salt solution is 25℃, and the power supply is 30V;

[0065] The distance between the steel bar and the anode material is 30 cm;

[0066] The anode material is graphite;

[0067] S4. Drying: After the inorganic salt protective layer is formed on the surface of the steel bar, the steel bar is washed with water and dried; the drying temperature is 30°C and the time is 20 minutes.

[0068] Example 2

[0069] This embodiment provides a method for improving the corrosion resistance of steel bars in concrete, comprising the following steps:

[0070] S1. Pre-treat the surface of the steel bar: the steel bar is degreased, pickled, washed, and sandblasted before use; the degreasing step is to ultrasonically clean the steel bar in a sodium hydroxide solution with a mass concentration of 5% for 15 minutes at a degreasing temperature of 30°C; the pickling step is to soak the degreased steel bar in a 0.2 mol / L dilute hydrochloric acid solution for 10 minutes;

[0071] S2. preparing an inorganic salt solution: adding zinc sulfate to water to prepare an inorganic salt solution; the concentration of zinc sulfate in the inorganic salt solution is 0.25 mol / L;

[0072] S3, cathode electrodeposition: placing the steel bar in a zinc sulfate solution and placing the anode material in an inorganic salt solution; connecting the steel bar and the anode material to the negative electrode and the positive electrode of a power source respectively, and performing electrodeposition to form an inorganic salt protective layer on the surface of the steel bar;

[0073] The process parameters of electrodeposition control are: cathode current density is 0.8A / m 2 , the deposition time is 90 min, the temperature of the inorganic salt solution is 25 ° C, and the power supply is 20 V;

[0074] The distance between the steel bar and the anode material is 30 cm;

[0075] The anode material is graphite;

[0076] S4. Drying: After the inorganic salt protective layer is formed on the surface of the steel bar, the steel bar is washed with water and dried; the drying temperature is 50°C and the time is 15 minutes.

[0077] Performance Testing

[0078] Figure 1 The surface morphology of the steel bar before electrodeposition treatment and after treatment according to the method in Examples 1 to 2.

[0079] Figure 1 After sodium sulfate electro-deposition treatment, it means the steel bar is treated according to the method in Example 1, and after zinc sulfate liquid electro-deposition treatment, it means the steel bar is treated according to the method in Example 2.

[0080] from Figure 1 It can be seen that after the electrodeposition treatment, a deposited salt protective layer will be generated on the surface of the steel bar. The deposited salt protective layer in the sodium sulfate solution is thinner, darker in color, and rougher than the protective layer in the zinc sulfate solution.

[0081] Figure 2 It shows the surface microscopic morphology of steel bars that have not been treated with electrodeposition and steel bars treated according to the methods in Examples 1 to 2 after being placed in a salt spray environment (ambient temperature is (35±2)°C, relative humidity is greater than 95%, and salt spray mass concentration is 5%±1%) for 7 days.

[0082] Figure 2 The non-electrodeposition treatment refers to the steel bars that have not been subjected to the electrodeposition treatment, the sodium sulfate electrodeposition treatment refers to the steel bars treated according to the method in Example 1, and the zinc sulfate liquid electrodeposition treatment refers to the steel bars treated according to the method in Example 2.

[0083] from Figure 2 It can be seen that after being placed in a salt spray environment, large areas of rust appeared on the surface of the steel bars that were not treated with electrodeposition, while no obvious rust appeared on the surface of the steel bars treated with electrodeposition.

[0084] Figure 3 is the linear polarization curve of the steel bar before electrodeposition treatment.

[0085] Figure 4 is the linear polarization curve of the steel bar after being treated according to the method in Example 1.

[0086] Figure 5 is the linear polarization curve of the steel bar after being treated according to the method in Example 2.

[0087] Among them, the polarization curve test method is to use an electrochemical workstation with a three-electrode system for testing, with a scanning range of ±10mV and a scanning frequency of 0.1mV / s. The working electrode is the steel bar before deposition treatment or the steel bar treated according to the method in Examples 1 to 2. The reference electrode is a saturated calomel electrode, and the counter electrode is a stainless steel sheet.

[0088] from Figures 3 to 5 It can be seen that the self-corrosion potential of the steel bar increases when treated according to the methods of Examples 1 to 2. The self-corrosion potential of the reference steel bar without electrodeposition treatment is about -0.663 V, while the self-corrosion potential of the steel bar after electrodeposition treatment with sodium sulfate solution is increased to -0.392 V, and the self-corrosion potential of the steel bar after electrodeposition treatment with zinc sulfate solution is increased to -0.286 V. The higher the self-corrosion potential, the better the corrosion resistance of the steel bar. This shows that the method of the present invention can greatly improve the corrosion resistance of the steel bar.

[0089] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0090] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A method for improving the corrosion resistance of steel bars in concrete, characterized in that: The following steps are involved: Adding an inorganic salt into water to prepare an inorganic salt solution; The steel bar is placed in an inorganic salt solution, and an anode material is placed in the inorganic salt solution; The steel bar and the anode material are connected to the negative electrode and the positive electrode of the power supply respectively to perform electrodeposition to form an inorganic salt protective layer on the surface of the steel bar; Wherein, the inorganic salt includes at least one of calcium sulfate, zinc sulfate, sodium sulfate, calcium chloride and calcium acetate.

2. The method for improving the corrosion resistance of steel bars in concrete according to claim 1, characterized in that: The concentration of the inorganic salt in the inorganic salt solution is 0.1-2 mol / L.

3. The method for improving the corrosion resistance of steel bars in concrete according to claim 1, characterized in that: The process parameters of electrodeposition control are: cathode current density is 0.75~5A / m 2 , the deposition time is 1 to 24 hours, the temperature of the inorganic salt solution is 20 to 30°C, and the maximum power supply voltage does not exceed 50V.

4. The method for improving the corrosion resistance of steel bars in concrete according to claim 1, characterized in that: Before placing the steel bar in the inorganic salt solution, the steel bar is also pre-treated, and the pre-treatment includes: degreasing, pickling, water washing, and sandblasting the steel bar in sequence for use.

5. The method for improving the corrosion resistance of steel bars in concrete according to claim 4, characterized in that: The oil removal is specifically: Place the steel bars in an alkali solution and perform ultrasonic treatment at 20-30°C.

6. The method for improving the corrosion resistance of steel bars in concrete according to claim 4, characterized in that: The pickling is specifically as follows: Soak the degreased steel bars in a hydrochloric acid solution with a concentration of 0.1 to 0.2 mol / L for 10 to 20 minutes.

7. The method for improving the corrosion resistance of steel bars in concrete according to claim 5, characterized in that: The alkali solution includes at least one of a sodium hydroxide solution, a sodium carbonate solution, a sodium phosphate solution, and a sodium silicate solution; The mass concentration of the alkali solution is 2 to 10%; The ultrasonic treatment time is 10 to 15 minutes.

8. The method for improving the corrosion resistance of steel bars in concrete according to any one of claims 1 to 7, characterized in that: After the inorganic salt protective layer is formed on the surface of the steel bar, the steel bar is washed and dried; The drying temperature is 30-50°C and the drying time is 15-60 minutes.

9. The method for improving the corrosion resistance of steel bars in concrete according to any one of claims 1 to 7, characterized in that: The distance between the steel bar and the anode material is 10 to 50 cm.

10. The method for improving the corrosion resistance of steel bars in concrete according to any one of claims 1 to 7, characterized in that: The anode material includes at least one of graphite and stainless steel.